Cobalt catalysts for the oxidation of diesel soot particulate - Harrison, Philip G. (2003)
Ceria-supported materials prepared by three routes, coprecipitation from aqueous solution containing both Co2+ and Ce3+ ions, and impregnation of preformed ceria gel with either cobalt(II) nitrate or cobalt(II) acetate, have been investigated for catalytic activity towards oxidation of diesel soot. All three materials catalyze the conversion of diesel soot particulate to carbon dioxide under a flow of either 6 vol.% O2 or 0.5 vol.% NO + 6 vol.% O2 in helium in the temperature range 573?613 K. The temperature of maximum conversion rate shows a small dependence on the particular catalyst and the composition of the oxidant. Raman spectroscopy of the ceria-supported cobalt catalysts indicate that the cobalt is present as Co3O4, but its average particle size in Co/CeO2 impregnated with Co acetate is smaller than the other two Co/CeO2 preparations. Features in the temperature-programmed reduction (TPR) profiles in the range 500?600 K, coincident with the temperature of catalytic activity, appear to be associated with reduction of the cobalt, suggesting a redox-type mechanism assisted by oxygen spillover on the CeO2 support. In contrast, cobalt supported on alumina, silica, and tin(IV) oxide obtained by coprecipitation show much lower activity due to the presence of dispersed Co2+ ions in these materials although small amounts of Co3O4 may be present on alumina and tin(IV) oxide.